Protective role of Eurycoma Longifolia Jack root extract against high-fat diet induced testicular damage in sprague-dawley rats - Al-Ani, Imad M Al-Ani; Ku Zaifah, Norsidah; AlJoufi, Fakhria A. AlJoufi; Mokhtar, Rafidah H.Mokhtar; A. Talib, Norlelawati A. Talib; Faisa, Ghasak Ghazi Faisa (Pharmacognosy Journal, 2019)
Objective: The aims of this study were to investigate the adverse effects of the high-fat-diet (HFD) on the testosterone level and testicular structure of male rats as well as to examine whether Eurycoma Longifolia (EL) is able to ameliorate these effects. Methods: Twenty-four male Sprague-Dawley (SD) rats were divided into four groups each containing 6 rats. Group ND was given only normal diet, group NDEL was given normal diet and EL extracts (15 mg/ kg) dissolved in distilled water, group HFD was given only high-fat-diet and group HFDEL was given high-fat-diet and EL extracts (15 mg/kg). EL was administered orally for 12 weeks. The animal’s testosterone level was measured at week 0, 6 and 12. The rats were sacrificed at the end of 12th weeks and the testes samples were processed for histological examination Results: The testosterone level was significantly increased (p < 0.05) in the in the treated rats with EL (NDEL and HFDEL) compared with ND and HFD groups. Treatment with HFD revealed a marked degeneration of the seminiferous tubule epithelium and disruption of interstitial cells of the testis thereby interfering with spermatogenesis. Treatment of HFD rats with El reduced the adverse effects of HFD and improved the morphological structure of the seminiferous tubules. Conclusion: These findings revealed that EL has ameliorative effects against the testicular damage caused by high-fat-diet.